Immunogenicity of four doses of oral poliovirus vaccine when co-administered with the human neonatal rotavirus vaccine (RV3-BB). Issue 49 (20th November 2019) - Cowley, Daniel; Sari, Rini Mulia; Handley, Amanda; Watts, Emma; Bachtiar, Novilia S.; At Thobari, Jarir; Satria, Cahya Dewi; Bogdanovic-Sakran, Nada; Nirwati, Hera; Orsini, Francesca; Lee, Katherine J.; Kirkwood, Carl D.; et al.
Highlights: Both OPV and rotavirus vaccines contain live, attenuated strains that replicate in the gut. OPV and rotavirus vaccine co-administration has been associated with lower rotavirus immune responses. RV3-BB is a novel human neonatal rotavirus vaccine that provides protection from rotavirus disease from birth. OPV and RV3-BB co-administration did not reduce immunogenicity of either vaccine. These findings support the use of RV3-BB where either OPV or IPV is used in the routine schedule. Abstract: Background: The RV3-BB human neonatal rotavirus vaccine was developed to provide protection from severe rotavirus disease from birth. The aim of this study was to investigate the potential for mutual interference in the immunogenicity of oral polio vaccine (OPV) and RV3-BB. Methods: A randomized, placebo-controlled trial involving 1649 participants was conducted from January 2013 to July 2016 in Central Java and Yogyakarta, Indonesia. Participants received three doses of oral RV3-BB, with the first dose given at 0–5 days (neonatal schedule) or ~8 weeks (infant schedule), or placebo. Two sub-studies assessed the immunogenicity of RV3-BB when co-administered with either trivalent OPV (OPV group, n = 282) or inactivated polio vaccine (IPV group, n = 333). Serum samples were tested for antibodies to poliovirus strains 1, 2 and 3 by neutralization assays following doses 1 and 4 of OPV. Results: Sero-protective rates to poliovirus type 1, 2 or 3 were similar (range 0.96–1.00) after four doses of OPV co-administered with RV3-BB compared with placebo. Serum IgA responses to RV3-BB were similar when co-administered with either OPV or IPV (difference in proportions OPV vs IPV: sIgA responses; neonatal schedule 0.01, 95% CI −0.12 to 0.14; p = 0.847; infant schedule −0.10, 95% CI −0.21 to −0.001; p = 0.046: sIgA GMT ratio: neonatal schedule 1.23, 95% CI 0.71–2.14, p = 0.463 or infant schedule 1.20, 95% CI 0.74–1.96, p = 0.448). Conclusions: The co-administration of OPV with RV3-BB rotavirus vaccine in a birth dose strategy did not reduce the immunogenicity of either vaccine. These findings support the use of a neonatal RV3-BB vaccine where either OPV or IPV is used in the routine vaccination schedule.